CHRONIC FATIGUE SYNDROME - ANY PROGRESS - Sharpe, M (1995)
A new international definition of chronic fatigue syndrome employs an epidemiological perspective. Studies in nonspecialist settings confirm the association of the symptom of chronic fatigue with depression but also reveal that the physical illness attribution, typical of hospital-referred patients and associated with a poor prognosis, is relatively uncommon in primary care. It is concluded that further efforts at classification and treatment of patients suffering from chronic unexplained fatigue should take the patients' beliefs, behaviour and emotional state into account as well as their somatic symptoms.